Performing comparative advantage: The case of the global coffee business - Pierpaolo Andriani; Carsten Herrmann-Pillath (Frankfurt School of Finance & Management, 2011)
We posit that comparative advantage is discovered via alternative transactional regimes of trading. Transactional regimes are performative, based on different forms of embedded agency. The theory is applied on a study of Brazilian coffee business which manifests the increasing importance of specialty coffee. Innovations in the transactional regime have created new forms of agency which triggered new ways to produce coffee and to activate the hidden potential of variety in consumer tastes. Comparative advantage, though still driven by endowments with natural resources, relates with very different product characteristics and forms of market organization. This constitutes the performativity of comparative advantage.
Keywords: B52; F10; F14; O10; 330; comparative advantage; trading; transactional regimes; performativity; coffee